Constructing A Scale Based on Dramatic Representation of The Sociological and Psychological Skills of Students with Autism Spectrum Disorders and Verifying Its Psychometric Properties - Friehat, Halaa Abdalmohde Hssien; Fraihat, Nesreen Bassam; Alhenawi, Esraa; Alkisbeh, Esraa Mahmoud Abdeljalil (International Journal of Membrane Science and Technology, 2023)
The current study aimed to construct a measure based on dramatization of the sociological and psychological skills of students with autism spectrum disorders, in light of the variables of gender and group (experimental and control), and to verify its psychometric characteristics. The sample of the study consisted of (50) male and female students with autism spectrum disorders who were selected in a simple random manner. The sample was distributed into two groups. The experimental group amounted to (25), and the control group amounted to (25). The results of the study showed that there were statistically significant differences at the significance level (? ? 0.05) in the students’ performance on the immediate post-measurement in favor of the experimental group, and there were no statistically significant differences at the significance level (? ? 0.05). ? ? 0.05) in the students' performance of the sociological and psychological skills between the two measurements; The immediate and post-deferred dimensions of the experimental group, which gives an indication of the effectiveness of the scale of the sociological skills of students with autism spectrum disorders, and the current study, based on several indicators extracted from the SPSS program, concluded that the scale of the current study was judged with honesty in data representation, as well as with a high level of stability.